2019
DOI: 10.1029/2019jc015281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Beaufort Gyre Freshwater Content in 2003–2018

Abstract: Hydrographic data collected from research cruises, bottom-anchored moorings, driftingIce-Tethered Profilers, and satellite altimetry in the Beaufort Gyre region of the Arctic Ocean document an increase of more than 6,400 km 3 of liquid freshwater content from 2003 to 2018: a 40% growth relative to the climatology of the 1970s. This fresh water accumulation is shown to result from persistent anticyclonic atmospheric wind forcing accompanied by sea ice melt, a wind-forced redirection of Mackenzie River discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
240
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(261 citation statements)
references
References 90 publications
20
240
1
Order By: Relevance
“…For example, the accumulation of fresh water requires the availability of fresh water (e.g., sea‐ice melt water or river influxes) to coincide with atmospheric forcing that drives Ekman convergence in the surface ocean layer. Proshutinsky et al () show that the dominant contributions to recent freshwater accumulation in the Beaufort Gyre have been Pacific Water inflows through Bering Strait and fresh water from the Mackenzie River; changes to either could yield changes in Beaufort Gyre freshwater content even while the atmospheric forcing remains the same. We revisit changes in Beaufort Gyre fresh water in section .…”
Section: The Beaufort Gyrementioning
confidence: 99%
See 2 more Smart Citations
“…For example, the accumulation of fresh water requires the availability of fresh water (e.g., sea‐ice melt water or river influxes) to coincide with atmospheric forcing that drives Ekman convergence in the surface ocean layer. Proshutinsky et al () show that the dominant contributions to recent freshwater accumulation in the Beaufort Gyre have been Pacific Water inflows through Bering Strait and fresh water from the Mackenzie River; changes to either could yield changes in Beaufort Gyre freshwater content even while the atmospheric forcing remains the same. We revisit changes in Beaufort Gyre fresh water in section .…”
Section: The Beaufort Gyrementioning
confidence: 99%
“…Between 1992 and 2012 Arctic Ocean total freshwater content (integrated fresh water relative to a salinity of 34.8) increased at a rate of around 600±300 km 3 year −1 ; about two thirds has been attributed to salinity decreases, with the remainder a result of a thickening of the freshwater layer (Carmack et al, ; Haine et al, ; Rabe et al, ). The most comprehensive in situ hydrographic measurements are from the Beaufort Gyre region where observations indicate an overall increase in total freshwater content by almost 40% since the 1970s (from around 17×10 3 km 3 to 23.5×10 3 km 3 in 2018) (Proshutinsky et al, , ). Such increases are associated with the strengthening of the Beaufort Gyre responding to anticyclonic wind forcing over the Canadian Basin, freshwater accumulation from sea‐ice melt, increasing freshwater flux through Bering Strait, and greater influence of Mackenzie River water (Krishfield et al, ; Proshutinsky et al, , ).…”
Section: Arctic Ocean Variability Climate Change and Future Perspecmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical changes that occurred in 1948-2013 were examined by Proshutinsky et al (2015), and the analysis was extended to recent years in this special collection (Proshutinsky, Krishfield, Toole, et al, 2019). Proshutinsky, Krishfield, Toole, et al (2019) show that the last two decades of sustained anticyclonic wind forcing in the region (1997-2018) differ significantly from the climatology shown in Figure 2. In addition, it was found that seasonal change in Beaufort Gyre total freshwater content ranges from 5 to 10% of the total freshwater content (depending on the intensity and sense of the atmospheric circulation); interannual changes can amount to as much as 1,500 km 3 (around 8% of the total on average); decadal changes were approximately 1,000 km 3 per decade prior to 2000; an accelerated rate of increase of about 4,000 km 3 per decade characterizes the period since 2003; during 2003-2008, the Beaufort Gyre geostrophic circulation has intensified (Armitage et al, 2016(Armitage et al, , 2017McPhee, 2013;McPhee et al, 2009); and the baroclinic component of the Transpolar Drift current intensified and shifted toward Canada, accelerating sea-ice drift.…”
Section: Beaufort Gyre Observing Systemmentioning
confidence: 99%
“…Changes in net precipitation/evaporation affect TA through dilution/concentration, but such changes tend to be very localized, and can easily be accounted for by normalizing TA to salinity (Woosley et al 2016). Increases in other freshwater inputs such as river runoff and sea-ice melt would dilute TA, and both are known to be increasing in the western Arctic (Jones et al 2008;Yamamoto-Kawai et al 2009;Newton et al 2013;Carmack et al 2016;Proshutinsky et al 2019;Zhong et al 2019). Surface ocean waters entering the Arctic from the Pacific have a TA around 2200 μmol kg −1 , and deeper Atlantic derived waters are~2300 μmol kg −1 .…”
Section: Arctic Fresheningmentioning
confidence: 99%